Inside Cover: Implications of Quenching‐to‐Dequenching Switch in Quantitative Cell Uptake and Biodistribution of Dye‐Labeled Nanoparticles (Angew. Chem. Int. Ed. 28/2021). Issue 28 (17th May 2021) - Yang, Guangze; Liu, Yun; Hui, Yue; Tengjisi,; Chen, Dong; Weitz, David A.; Zhao, Chun‐Xia
Abstract : A quenching‐to‐dequenching switch of fluorescence‐labeled nanoparticles in biological environments is unveiled by Chun‐Xia Zhao and co‐workers in their Research Article on page 15426 . With dye molecules in a solid state, the release and/or degradation of the dye‐labeled nanoparticles in biological environments led to a several‐fold increase in fluorescence intensity due to the state switch, which has significant implications in quantitative cell uptake and biodistribution studies.